2022
DOI: 10.1097/j.pain.0000000000002582
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Karlsen et al. Consensus on a core outcome set: a panel decision

Abstract: We are grateful for the letter from Karlsen et al., 4 that raised a very interesting point related to our previously published articles in PAIN. 1,6 Within these articles (and another one published recently by us as well 5 ), we systematically investigate outcome domains assessed in prospective interventional clinical trials regarding pain management after total knee arthroscopy (TKA 1 ) and sternotomy. 5 These data were consecutively used to develop a Core Outcome Set (COS) of domains referring to perioper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Notably, there remain different aspects to address are currently used scoring systems sufficiently precise in specific subgroups (e.g., gender [Tafelski et al, 2016]), in specific settings (e.g. nursing homes [Kutschar et al, 2022]) and feasible tools in core outcome sets of patient-reported pain measurement (Bigalke et al, 2021;Elbers et al, 2022;Pogatzki-Zahn, 2022)? We thank Siamak Sabour for the stimulating scientific discussion.…”
Section: E T T E R T O T H E E D I T O R Authors' Reply To the Commen...mentioning
confidence: 99%
“…Notably, there remain different aspects to address are currently used scoring systems sufficiently precise in specific subgroups (e.g., gender [Tafelski et al, 2016]), in specific settings (e.g. nursing homes [Kutschar et al, 2022]) and feasible tools in core outcome sets of patient-reported pain measurement (Bigalke et al, 2021;Elbers et al, 2022;Pogatzki-Zahn, 2022)? We thank Siamak Sabour for the stimulating scientific discussion.…”
Section: E T T E R T O T H E E D I T O R Authors' Reply To the Commen...mentioning
confidence: 99%